Teachers' use of assessment data for instructional decision making. Issue 4 (21st April 2022) - Choi, Kyong Mi; Hwang, Jihyun; Jensen, Jessica; Hong, Dae S.
Abstract : Summative assessment data are rarely adapted into instructional decision making. In this project, teachers and researchers work together to identify how teachers use diagnostic data (students' development of common core standards). We analysed students' responses to trimester tests that teachers and researchers modified together using cognitive diagnosis modelling approach. Teachers' use of diagnostic data was explored through interviews and observations. It was found that teachers tended to use provided information in reactive ways. Teachers tried to confirm their existing opinions about individual students' performance.